The Utilization of Cultural Movements to Overcome Stigma in Narrative of Postnatal Depression - Elliott, Grace K.; Millard, Chris; Sabroe, Ian (Frontiers in Psychiatry, 2020)
BACKGROUND Despite affecting 15% of new mothers, experience of postnatal depression has often been hidden by stigma, cultural beliefs, and lack of medical understanding. We examined the barriers to women sharing their experience and gaining help, using their own words to illuminate the experiences of stigma and injustice. This study examines the narratives of women across the 20th century, explores cultural movements that framed and contextualized their experiences, and marks how women became more empowered to speak of maternal distress. METHODS Narrative literature was identified via searches of literature catalogues. Narrative accounts provided a lens through which to analyze cultural understandings of postnatal depression according to historical method. Contemporary medical and sociological literature discussing postnatal depression was used to contextualize the social climate within which these narratives were written. This work combines historical analysis with philosophical framework to develop insight into patient experiences of mental ill-health and associated stigma. RESULTS This research identified three core cultural movements providing women with a framework in which to discuss their experiences of postnatal depression: the labor movement in the early twentieth century, the second-wave feminism movement in the mid-twentieth century (c. 1960-1980), and the so-called ‘Prozac revolution’ emerging at the end of the twentieth century. These movements provided distinct culturally acceptable etiologies around which women were able to frame their experience of postnatal depression. This provided women with space in which to share and process their experiences, and aided them in overcoming contemporary stigma against mental illness by challenging disparaging stereotypes of the depressed mother. CONCLUSIONS Despite the stigmatizing nature of mental illness, women have demonstrated resilience and ingenuity by utilizing acceptable cultural movements to reframe their experiences of postnatal depression, challenging traditional perceptions of motherhood and effectively earned recognition of their sufferings. During this period, concordance between patient perceptions of postnatal depression and clinical understandings of the condition has been variable. Highlighting the detriment to therapeutic relationship when discordance is present, the narrators have demonstrated the need to destigmatize illness and facilitate cooperation between physician and patient, and remind clinicians of the importance of placing patient experience at the center of care.